PERILAKU KONSUMEN KOPI DI MASA PANDEMI COVID-19 (Suatu Kasus Pada Mahasiswa Fakultas Pertanian Universitas Padjadjaran) - Raden Ajeng Sukma Ayu Hanipradja; Elly Rasmikayati; Bobby Rachmat Saefudin (Universitas Galuh, 2022)
Students are among those who like to consume coffee in gatherings in coffee shops, but this has been hampered since the Covid-19 pandemic was due to the implementation of the Large-Scale Social Restrictions policy which prohibits gathering activities to prevent the spread of the virus. The purpose of this study was to determine whether or not there was a change in student behavior in consuming coffee during the Covid-19 pandemic. This study uses a quantitative descriptive design with a survey method. The research was conducted on students of the Faculty of Agriculture, Padjadjaran University. The analytical method used is descriptive statistics with diagrams, frequency distribution tables, box plots, and cross tabulations. The results showed a change in student behavior in consuming coffee during the Covid-19 pandemic. There is an increase in the frequency of respondents in the number of sources of information obtained, the number of places to buy coffee products visited, and the frequency in consuming coffee among students. There is a decrease in the frequency of respondents in the types of coffee products consumed, the amount of coffee consumed, and the level of satisfaction with coffee products among students. There is no change in the amount of fees paid by students for coffee products in one week.